Low-dose Buprenorphine Initiation in Hospitalized Adults With Opioid Use Disorder: A Retrospective Cohort Analysis. Issue 2 (17th March 2022) - Button, Dana; Hartley, Jennifer; Robbins, Jonathan; Levander, Ximena A.; Smith, Natashia J.; Englander, Honora
Abstract : Objectives: Patients with opioid use disorder (OUD) can initiate buprenorphine without requiring a withdrawal period through a low-dose (sometimes referred to as "micro-induction") approach. Although there is growing interest in low-dose buprenorphine initiation, current evidence is limited to case reports and small case series. Methods: We performed a retrospective cohort study of patients with OUD seen by a hospital-based addiction medicine consult service who underwent low-dose buprenorphine initiation starting during hospital admission. We then integrated our practice-based experiences with results from the existing literature to create practice considerations. Results: Sixty-eight individuals underwent 72 low-dose buprenorphine initiations between July 2019 and July 2020. Reasons for low-dose versus standard buprenorphine initiation included co-occurring pain (91.7%), patient anxiety around the possibility of withdrawal (69.4%), history of precipitated withdrawal (9.7%), opioid withdrawal intolerance (6.9%), and other reason/not specified (18.1%). Of the 72 low-dose buprenorphine initiations, 50 (69.4%) were completed in the hospital, 9 (12.5%) transitioned to complete as an outpatient, and 13 (18.1%) were terminated early. We apply our experiences and findings from literature to recommendations for varied clinical scenarios, including acute illness, co-occurring pain, opioid withdrawal intolerance, transition from high dose methadone to buprenorphine, history of precipitated withdrawal, and rapid hospital discharge. We share a standard low-dose initiation protocol with potential modifications based on above scenarios. Conclusions: Low-dose buprenorphine initiation offers a well-tolerated and versatile approach for hospitalized patients with OUD. We share lessons from our experiences and the literature, and provide practical considerations for providers.